Knowledge, attitude and practice of Sari birth cohort members during early weeks of COVID-19 outbreak in Iran - Leila Shahbaznejad; Mohammad Reza Navaeifar; Faeze Sadat Movahedi; Fatemeh Hosseinzadeh; Seyed Alireza Fahimzad; Zahra Serati Shirazi; Mohammad Sadegh Rezai (BMC, 2021)
Abstract Background It has been determined that the coronavirus disease 2019 (COVID-19) pandemic needs social distancing and proper measures to prevent its spreading. This study aimed to determine COVID-19 knowledge, attitude, and practice among Sari Birth Cohort (SBC) members. Methods In this cross-sectional study linked to the SBC in north of Iran, mothers living in Sari and its suburbs from March 28 to April 8, 2020 were evaluated. The measurement tool was an online researcher-made, self-reported knowledge, attitude, and practice questionnaire related to COVID-19. Results In total, 1449 mothers with a mean age of 31.51 ± 5.73 years participated. Of them, 82.4% had good knowledge (98.6% in healthcare workers and 79.2% in housewives, p = 0.000). Most of them were worried about spread of the disease in the country (97.4%) and agreed that COVID-19 will finally be successfully controlled around the world (72.2%). Sleep disturbance was reported in 42.7% of mothers. Eighty-eight percent of cases wore masks and gloves when leaving home, 99.4% washed their hands frequently while 12.9% went to any crowded places. People with better knowledge followed safer practices (p = 0.000) and were more worried about the spread of the disease in the country and infection (among themselves and their first-degree relatives) (p = 0.000). Conclusions Most of the SBC members had a good level of knowledge about COVID-19 but were worried about a long-term pandemic period. They also had good practices regarding the prevention of the disease.